The collectivist approach of Makarenko as a conribution in the training of the educate - Ventura-Echevarria, Marco A. (2023)
The present investigation entitled "Makarenko's collectivist approach as a contribution to the formation of the student" had as its starting point the construction of Makarenko's pedagogical thought, precisely, we approached it in the context of the Russian revolution. Immediately we reaffirm that Makarenko embraced a scientific conception of the world, I mean dialectical materialism, a philosophical method that allowed him to know his objective reality and transform it, all this points to the relationship between theory and practice or saying and doing; Consequently, it implies turning bad into good, that is the work for results that modern society demands. The pedagogue masterfully created and applied the collectivist method, a transformative method, which gives education the mass character. At the same time, Makarenko has the merit of having masterfully transmitted pedagogical knowledge, teaching the learner to think and reason. But this was not achieved at once, but through several periods of doubts and torturing errors, making it clear that after several attempts victory is achieved. In this sense, he discovered that in order to work successfully in the school, it was not only necessary to teach, but also to know how to educate, taking into account the individual characteristics and potential of each student. It should be noted that Makarenko's educational work was carried out in the midst of enormous difficulties, such as children and young delinquents (offenders of the law), economic crisis and period of wars. Makareko's teaching, for those of us who are heading to teaching work, lies in the following, to educate everyone at the same time, and not each one separately, one must have the necessary perspective, equally understandable to all. At the same time, do not think that you educate the child only when you talk to him, reprimand him or command him. You educate him at every moment of his life, even when he is not at home with you. How they talk to other people and about other people, how they are happy or sad, their way of treating friends and enemies, how they laugh, how they read the press are details that are all very important for the child. So the training that the teacher and the parents exercise regarding the student is permanent and crucial in the lives of the children.